2017
DOI: 10.21475/ajcs.2017.11.01.pne226
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by trait biplot analysis to study associations and profiles of Ethiopian white lupin (Lupinus albus L.) landraces

Abstract: Limited information is available on trait relations and profiles of white lupin landraces in tropical growing conditions including Ethiopia. The objectives of this study were to understand the relationships among traits, and to document trait profile of Ethiopian white lupin landraces. As a component of this study, two sets of experiments were conducted. The first comprehensive experiment that consisted of 143 accessions collected from major lupin growing areas of Ethiopia was evaluated at Merawi and the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The most representative variables are those that form the smallest angles with the line that presents the circle formed with the arrow, i.e., with the medium [31]. In addition, the ideal variable should be able to discriminate genotypes and represent the other characteristics, thus, it should present high CP1 (greater discriminatory capacity) and low CP2 (greater representativity) [28,29] Studies with Capsicum using biplot analysis are not yet described in the literature, however, recent studies have reported success in discriminating promising genotypes in other cultures, based on this type of graph, with PC values ranging from 60 to 80% [29,32].…”
Section: Resultsmentioning
confidence: 99%
“…The most representative variables are those that form the smallest angles with the line that presents the circle formed with the arrow, i.e., with the medium [31]. In addition, the ideal variable should be able to discriminate genotypes and represent the other characteristics, thus, it should present high CP1 (greater discriminatory capacity) and low CP2 (greater representativity) [28,29] Studies with Capsicum using biplot analysis are not yet described in the literature, however, recent studies have reported success in discriminating promising genotypes in other cultures, based on this type of graph, with PC values ranging from 60 to 80% [29,32].…”
Section: Resultsmentioning
confidence: 99%
“… This map is “Reprinted from [ 33 ] under a CC BY license, with permission from [AJCS], original copyright [2017]”. …”
Section: Methodsmentioning
confidence: 99%
“…Genotypes with anthracnose resistance and late flowering cannot produce pods and fill seeds at the end of the season [ 82 ]. Moreover, the relationships among lupin traits are significantly influenced by the fluctuating conditions of the growing environments [ 90 , 91 ]. Thus, genotype selection should be based on multiple trait data in variable environments within the target regions [ 78 ].…”
Section: Breeding Of Lupinsmentioning
confidence: 99%